A novel frameshift variant in the TMPRSS3 gene causes nonsyndromic hearing loss in a consanguineous family - Nahid Rezaie; Saeedeh Sadat Ghazanfari; Seyede Mahsa Mousavikia; Nader Mansour Samaei; Morteza Oladnabi; Abdolazim Sarli; Teymoor Khosravi (BMC, 2024)
Abstract Background Hearing Loss (HL) is the most common sensorineural condition in humans. Mutations in the TMPRSS3 gene (DNFB8/10 locus) have been linked to autosomal recessive non-syndromic hearing loss (ARNSHL). Methods Whole-exome sequencing (WES) was utilized to identify disease-causing variants in a proband from Iran with ARNSHL who presented clinically with sensorineural, bilateral, and prelingual HL. The pathogenicity and novelty of the identified variant were assessed using various databases. A co-segregation study was also performed to confirm the presence of the variant in the proband's parents. Additionally, the secondary and tertiary structures of the mutant TMPRSS3 protein were predicted using bioinformatics tools. Furthermore, a global mutational spectrum of TMPRSS3 was created and statistically analyzed. The Iranome database was also used to identify other putative mutations in the TMPRSS3 gene in the Iranian population. Results We identified a novel homozygous single nucleotide deletion in TMPRSS3 (c.297delA, p.Asp100ThrfsTer52) in the proband. This is the first report of this mutation in a patient with ARNSHL. Sanger sequencing confirmed that this variant co-segregated from the proband's parents. Bioinformatic tools classified this novel variant as likely pathogenic. Additionally, 49.55% of families with TMPRSS3-related HL patients were shown to have consanguinity, consistent with our study. The Iranome database also revealed the c.268G > A variant as a putative novel mutation in TMPRSS3. Conclusion This research expanded the pool of evidence regarding the association between mutations in the TMPRSS3 gene and ARNSHL. The finding confirmed that a single nucleotide deletion caused HL in the proband, suggesting that genetic testing, such as WES, is a robust technique for diagnosing patients with this condition.